Analysis of LES-based combustion models applied to an acetone turbulent spray flame. Issue 1 (2nd January 2019) - Sacomano Filho, Fernando Luiz; Kadavelil, Jean; Staufer, Max; Sadiki, Amsini; Janicka, Johannes
ABSTRACT: Two different combustion models are analyzed for the prediction of an acetone turbulent diluted spray flame. Simulations are conducted in the Large Eddy Simulation (LES) framework, coupled with the Flamelet Generated Manifold (FGM) chemistry reduction method. To represent the polydispersed spray the Eulerian-Lagrangian specification is applied. Both combustion models consist of the Artificially Thickened Flame (ATF) and the presumed PDF approach. Effects of the evaporative cooling and the presence of droplets into the combustion modeling are accounted for. Results achieved with both models are validated against experimental data. These consist in statistical data of droplets velocities, liquid volumetric flux, a characteristic diameter, and temperature. A general good agreement with experimental data is observed. Analysis of simulations results allow deeper interpretation of additional flame features, for instance the double flame structure. As an outcome, the concept of the burning potential is introduced in this paper to assist the interpretation of the underlying mechanisms to the occurrence of different flame modes.